Solo : a Star Wars story [videorecording (Blu-Ray)] - Ehrenreich, Alden, 1989-; Harrelson, Woody; Clarke, Emilia, 1986-; Suotamo, Joonas, 1986- (Lucasfilm Ltd, 2019)
During an adventure into a dark criminal underworld, Han Solo meets his future copilot Chewbacca and encounters Lando Calrissian years before joining the Rebellion.